PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 019 KAMPUNG DAGANG KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Rahmadeni, Sarmudiah; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the facts that occurred in class IV SDN 019 Kampung Dagang, who showed symptoms of the students did not master the material science lessons have been learned. The problem of this research is "Does the implementation of inquiry learning strategies to improve learning outcomes for teaching science in class IV SDN 019 Kampung Dagang Kecamatan Rengat Kabupaten Rokan Hulu?". The purpose of this research to improve learning outcomes of science subjects class IV through the implementation of inquiry learning strategies (SPI) in SDN 019 Kampung Dagang Rengat District of Indragiri Hulu. This research is in in class IV SDN 019 Kampung Dagang and executed on April 5 to 22, 2016, with the number of subjects as many as 25 people consisting of 10 male students and 15 female students. This research is a classroom action research conducted in two cycles. Based on the results the learning outcomes in basic score, an average 73.2 increase in Deuteronomy Daily I to 82.2, with an increase to 12.2. In Deuteronomy Daily II increased to 87.8 with an increase of 6.8%. An overall increase of 19%. So we can conclude the implementation of inquiry learning strategies (SPI) can improve learning outcomes IPA in class IV SDN 019 Kampung Dagang Rengat District of Indragiri Hulu Keywords: Inquiry Learning Strategy, Learning Outcomes, IPA